The Cage Case. Arts and Social Neuroscience - Alfonso, Amendola; Camargo Molano, Jessica (Frontiers in Sociology, 2021)
The musician is John Cage whose production synthesizes and relaunches the entire system of the arts within the extraordinary tension of the avant-gardes. Apart from the socio-historical cross-section, Cage's experimentation is a pretext for reflecting on the artist’s work and the relationship between neuroscience and art. An important contribution to this topic comes from neuro-scientific-social research on new expressions "of creativity, imagination, genius". This study is based on the assumption that Cage was the forerunner of a neuronal experimentation that would be central in the experiments and research of many other artists. The theoretical reference model can be found in the research of the neuroscientist Kandel (2017), whose work was the starting point for this investigation. Kandel grasps the definitive break between scientific logic and humanistic sensitivity in the methodological reductionism practiced by neuroscience and in the experiments of contemporary creativity. Kandel found the use of memory, synthesis and knowledge of the world in authors such as Mondrian, de Kooning, Pollock, Rothko, Louis, Warhol and in the entire New York school of which Cage was an important member. The reflection on the relationship between art and neuroscience is synthetized in the avant-garde action of Cage and in all the artists who launched continuous attacks against the forms of tradition. The transition from figurative arts to abstraction is "comparable" to the reductionist process that is used in the scientific field to explain complexity and phenomenology. The prolegomena of this discourse are anticipated by a previous work written by Kandel in 2012 and can also be found in other studies on the relationship between neuroscience and art, in particular in the reflections of the neurobiologist and father of neuroaesthetics, Semir Zeki (2003). He analyzed artists’ work as a practice perfectly comparable to the research carried out by neuroscientists. Cage, the "case study" of this investigation, carried out a sound-stage-vision experience which, crossing theatre, media and arts, allows, at least, two definite perspectives: 1) to short-circuit the definitive subversion of “innate rules of perception” (Kandel); 2) to grasp a vivid and pulsating dimension of the relationship between art and neuroscience.